Combinatory interpretation of protein corona and shear stress for active cancer targeting of bioorthogonally clickable gelatin-oleic nanoparticles - Meghani, Nileshkumar M.; Amin, Hardik; Park, Chulhun; Cui, Jing Hao; Cao, Qing Ri; Choi, Kyung Hyun; Lee, Beom Jin (Materials Science and Engineering C, 2020)
Nanoparticle-protein interactions under conditions mimicking physiology determine how nanoparticles (NPs) will behave inside blood vessels and, therefore, the overall outcome of the drug-delivery system. Here, for the first time, we explore the effects of bio-mimicking shear stress and protein corona conditions on novel active targeting of clickable fattigation nanoparticles (NPs) for cancer therapy. Active targeting dibenzocyclooctyne-functionalized biocompatible gelatin-oleic NPs (GON-DBCOs) via a bioorthogonal click reaction were prepared by the desolvation method for delivery of docetaxel (DTX) to lung and breast cancer models. The effect of shear stress (5 dyne/cm2) and human serum albumin (HSA) protein corona on the cellular behavior of NPs was explored under a dynamic microfluidic system in lung (A549) and breast (MCF-7) cancer cell lines. The developed drug-loaded NPs had a particle size of 300 nm, a narrow size distribution, positive zeta potential, high encapsulation efficacy (72.4%), and spherical morphology. The particle size of the protein corona-coated NPs increased to 341 nm with a negative zeta potential. The inhibitory dose (IC50) increased approximately 3- and 42-fold in A549 and MCF-7 cells, respectively, under dynamic microfluidic conditions compared to static conditions. Cellular uptake was significantly decreased in the presence of shear stress and a protein corona, compared with static conditions, in both lung (A549, **p < 0.01) and breast (MCF-7, *p < 0.05) cancer cell lines. Clathrin-and energy-dependent pathways were found to be involved in the cellular uptake of NPs. This study could serve as a vital tool for the evaluation of NPs under aggressive bio-mimicking conditions comprising shear stress and a protein corona to predict the in vivo performance of NPs and support the preclinical and clinical translation of NP drug delivery systems.
Keywords: Cancer-targeting; Dynamic flows; Human serum albumins; Micro fluidic system; Narrow size distributions; Negative zeta potentials; Protein coronas; Spherical morphologies; Biocompatible Materials; Cell Line, Tumor; Cell Survival; Click Chemistry; Docetaxel; Drug Carriers; Drug Liberation; Gelatin; Humans; Microscopy, Confocal; Nanoparticles; Particle Size; Protein Corona; Serum Albumin, Human; Shear Strength; Active cancer targeting; Clickable fattigation nanoparticles; Dynamic flow; Human serum albumin; Protein corona; Shear stress